Instructional methods for students with learning and behavior problems - Schloss, Patrick J.; Sedlak, Robert A. (Boston : Allyn and Bacon, 1986)
This book presents teaching principles useful to general high school educators and special educators working with students demonstrating a variety of academic, behavioral, and social needs in secondary schools.
includes Bibliography.
Keywords: Children with disabilities -- United States. -- Education -- Curricula; Children with disabilities -- United States. -- Psychological testing; Criterion-referenced tests -- United States; Individualized instruction